Smart cereal: Healthy cereal innovation based on breadfurnish flour and trembesi seed flour as an alternative to prevent diabetes mellitus - Hanifah, Rofi Nur; Putri, Salsabila Tiara; Mustami'in, Yusron (Journal of Critical Ecology, 2024)
Background: Wheat is one of the staple foods in Indonesia. The demand for wheat increases along with the population growth. Unfortunately, the supply of wheat is quite limited. In addition, wheat has a high glycemic index so it is dangerous for consumption by people with diabetes mellitus. Based on this, it is necessary to make efforts to find alternative ingredients to replace wheat. Methods: The research method is a literature review.  Finding: The results of searches from various sources indicate that breadfruit and trembesi seeds can be processed into flour and used as a substitute for wheat. Breadfruit and trembesi seed has a low glycemic index content than wheat flour. Breadfruit flour and trembesi seed flour have the potential to be made into healthy cereals to prevent diabetes mellitus. Conclusion: Cereal from breadfruit and trembesi seed flour is healthier than cereal made from wheat flour. Novelty/Originality of this article: Until now, there has been no cereal made from the two ingredients we use, namely breadfruit and rain seeds. Both of these ingredients are easy to obtain, have a low glycemic index, and are safe for consumption by people with diabetes mellitus.